ANALISIS PENGARUH PDB, INFLASI, SUKU BUNGA, DAN KRISIS MONETER TERHADAP FDI DI INDONESIA TAHUN 1981- 2012 - Lembong, John David; SBM, Nugroho (Diponegoro Journal of Economics, 2013)
The role of FDI is really important to the country which the investment is developed. In addition to contributing to the transfer of capital, the establishment of the factory as a center of growth and employment, FDI also contributed to the transfer of management, science and technology, as well as the potential increase in state income taxes. This research aims to analyze the influence of GDP, inflation, interest rate, and monetary crisis to FDI in Indonesia. The method used is multiple linear regression with time series data from BPS between 1981-2012. The results of the regression shows that GDP has a positive effect on FDI, while Inflation and Interest Rates have no effect and the financial crisis negatively affect the development of FDI in Indonesia.